2011
DOI: 10.1109/tie.2011.2107715
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Load Frequency Control by PHEVs, Controllable Loads, and a Cogeneration Unit

Abstract: This paper presents a method for tracking a secondary frequency control (Load Frequency Control) signal by groups of plug-in hybrid electric vehicles (PHEVs), controllable thermal household appliances under a duty-cycle coordination scheme, and a decentralized combined-heat-and-power generation unit. The distribution of the control action on the participating units is performed by an aggregator utilizing a Model Predictive Control strategy which allows the inclusion of unit and grid constraints. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(132 citation statements)
references
References 26 publications
0
131
0
1
Order By: Relevance
“…It is aimed to aggregate and coordinate EV, so they can participate in intelligent charging schemes, e.g. ancillary services [18]. An EV coordinator is able to coordinate EV charging provided that the battery is in the linear SOC region.…”
Section: Ev Coordination and Ev Fleet Managementmentioning
confidence: 99%
“…It is aimed to aggregate and coordinate EV, so they can participate in intelligent charging schemes, e.g. ancillary services [18]. An EV coordinator is able to coordinate EV charging provided that the battery is in the linear SOC region.…”
Section: Ev Coordination and Ev Fleet Managementmentioning
confidence: 99%
“…Currently, the solely used and widely discussed appliance for this application is electric vehicles (EVs). Different types of electric vehicles (plug-in hybrid electric vehicles and "All-Electric" vehicles as classified by the U.S. DoE ("Hybrid and Plug-In Electric Vehicles" 2015)) can be applied for LFC as mobile BES units (Shimizu et al 2010;Galus, Koch, and Anderson 2011). According to the way of cooperation between controlled loads and power system operators, the strategy of loadscale systems can be classified into two groups: Coordinated Aggregate Systems and Non-Coordinated Individual Systems.…”
Section: Load-scale Systemsmentioning
confidence: 99%
“…Results showed that the frequency response is better without taking into account user convenience than when considering user convenience because, in the later case, the output of EVs is restricted by SOC limits. Provision of LFC utilizing the BESS of distributed Plug-in Hybrid Electric Vehicles (PHEV) along with thermostatically controlled loads has been proposed in (Galus, Koch, and Anderson 2011). Authors developed an aggregation method implemented through a management system defined as the aggregator based on model predictive control method.…”
Section: Coordinated Aggregate Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the private vehicles stop at the unit's parking lot and residential parking lot, they will be charged for a long period, so electric vehicles can be charged fully and this case is the type 1 charging behavior. The supermarket parking lot is restricted by the charging duration and this case is the type 2 charging behavior [9,10]. The charging sites and charging type of electric private vehicles is shown as the Fig.…”
Section: Driving and Charging Features Of Private Electric Vehiclesmentioning
confidence: 99%